Private management of public schools – contributions from a critical literature review (Práxis Educativa, 2025)
In recent years, we have observed a global trend towards the involvement of non-state actors in the provision of public services. Hybrid schools – charter schools (Canada, Colombia, United States, New Zealand), academies (England), or friskolor (Sweden) – are emblematic examples of such partnerships. This critical literature review aims to: identify the main characteristics of these school models; analyze the consequences of their implementation in different educational systems; and reflect on the main findings and recommendations made by researchers regarding their implementation or maintenance. The analysis of the model was organized into three categories: a) Expanding models (United States, England, and Sweden); b) Restricted models (Colombia and Canada); and c) Extinct models (New Zealand and Brazil). We analyzed the characteristics of charter schools considering the assumptions advocated by their proponents: financial efficiency and reduction of public spending; better teachers and improved working conditions; better student performance; greater autonomy; freedom of choice, segregation, and equity. We also identified seven key aspects that summarize the researchers’ suggestions concerning solutions found to mitigate the problems that arose with these schools. We concluded that this public-private partnership, as a pathway to the privatization of public education, has predominantly had a direct impact on increasing segregation and reducing the principles of democracy and equity in the educational systems where it was implemented.Keywords: Charter schools. Public-private partnerships. Privatization.